Over a million students use our free study notes to help them with their homework
The aim of this question is to end up with 'x' standing by itself on one side of the equation. The key principle to achieve this is to understand that whatever you do to one side of the equation, you have...
Let’s call (f(x)=2x+c) equation 1, (g(x) = cx+5) equation 2 and (fg(x)= 6x+d) equation 3.Start by finding fg(x) in terms of c by substituting (equation 2) into (equation 1) to get (fg(x)= 2(cx +5) +...
x=-4, x=3
When solving simultaneous equations our goal is always to use the equations given, which each have two unknowns in them, in order to find an equation with only one unknown. In this example, we can see tha...
←
510
511
512
513
514
→
Internet Safety
Payment Security
Cyber
Essentials